What do parents learn by reading a DPT vaccine information form? - Gold, Ronald (Pulsus Group Inc, 1994)
OBJECTIVE: Information forms are commonly used to inform parents about childhood vaccination. This study assessed the knowledge of mothers about pertussis and pertussis vaccine before and after reading a form about diphtheria-pertussis-tetanus (dpt) vaccine. DESIGN: A test was administered to mothers before and after the first vaccination of their infant. By random allocation, one-half of the mothers received the form (study group) in addition to the routine counselling by a public health nurse given to the others (control group). SETTING: Public health immunization clinics in suburban Vancouver, British Columbia. SUBJECTS: One hundred and fifty-one mothers who were scheduled to bring their infant for the first dpt immunization were recruited, of whom 145 (96%) completed the study. INTERVENTIONS: A test consisting of 20 true/false questions was administered by telephone two weeks before and two weeks after the first dpt vaccination. Additional data about sources of vaccine information, maternal education, number of children and maternal age were obtained. OUTCOME MEASURES: Mean scores and mean change in scores on test. RESULTS: The mean changes in scores between tests 1 and 2 in study and control groups were +22.2% and +6.9%, respectively, on the disease-related questions (P<0.001) and +14.6% and +10.7%, respectively, on the vaccine-related questions (P=0.16). The forms were considered to be very useful by the mothers and clearly enabled them to score higher on a test of their knowledge of pertussis and pertussis vaccine. CONCLUSIONS: Reading a dpt vaccine form enabled mothers to improve their knowledge of pertussis and pertussis vaccine.